RECORD OF THE OCEANIC SQUID SYMPLECTOTEUtTHIS OUALANIENSIS (LESSON) CAUGHT OFF MANGROL, SAURASHTRA COAST - Raje, S G; savaria, Y D (Indian Journal of Fisheries, 2011)
A female specimen of the oceanic squid Symplectoteuthis otialaniensis(Lesson) measuring 434 Imm in mantle length and 2.460 kg in weight caught bydrift net off Mangrol is: reported, giving the monphometrlc moasurements.A single female specimen of the oceanic squid Symplectoteuthis oulaniensis(Lesson) was caught in a drift gill net (150 mm mesh) off Mangrol, froman area 80 m in depth, it\ Saurashtra coast on February 6, 1986 (Fig. 1). Thespecimen measured 434 mm in dorsal mantle length and 2.460 kg in weight.Both the tentacles had been mutUated. The gonad was in maturing condition andthe gut was full with thoroughly macerated and pulpy food.